THE IMPORTANCE OF MOTIVATION IN FOREIGN LANGUAGE LEARNING - Abdukhakimova , Zebiniso Tulkinovna; Nurmamatova , Nodira Nuraliyevna; Burkhanova Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
English language education’s "neglected heart" has been described as motivation. Some teachers may need to pay more attention to the fact that all learning activities are filtered via the students’ motivation. In this way, students direct the flow of the classroom. There is no pulse; there is no life in the classroom if students are not motivated. Teachers who learn to use direct techniques to boost student motivation in their classrooms may become happier and more successful educators. The question of motivation is critical, particularly in English as a Foreign Language (EFL) contexts. Other aspects of teaching methodology appear to pale in comparison. Because of the harsh reality of learning English for most foreign language learners and students, it is critical to consider motivation as the essence of English language instruction.